Impact of glycerol on oil palm trunk starch bioplastics enhanced with citric-acid epoxidized palm oil oligomers - Hernando, Habib (2024)
Biodegradable bioplastics provide a promising solution to mitigate environmental harm from petroleum-based plastics. This study focuses on optimizing bioplastic films made from oil palm trunk starch (OPTS), using glycerol (10, 20, and 30 % v/w) as a plasticizer and modified with citric-acid epoxidized palm oil (CEPO). The bioplastics were formed using the solution casting method and analyzed for morphology, functional groups, diffraction peaks, thermal and mechanical properties, degradation time, and compostability. The optimal conditions were achieved with 30 % glycerol (Sample ST-CEPO-GLY30). The addition of glycerol enhances the thermal and mechanical properties, improves the biodegradability, and compostability of the bioplastics.